Usuń nawiasy i przeprowadź redukcję wyrazów opdobnych.
a) 3x+(2x+3y+1)
b) -4y+(-y+3)
c) 5a+(5-4a)
d) 2x-3+(x+4)
e) x-6y+(-3x+7y)
f) 2x-(3a-2)
g)a-(-2a+1)
h) 2y+6-(3y+5)
i) (3-2x)-(2x-3)
j) (x+2y-3)-(2x-3y+1)
k) -(2x-3y+4z)-(5x-6y+7z)
l) (2x-1)+(3x-2)-(4x-6)
ł) (-y+4)-(2y-1)+(3y+3)
m) (x-5)-(2x-1)-(-x+4)
n) (x-4y+1)-(x+3y-4)+(3x-y+5)
o) (8x-y)-(3x+y)-(-5x-2y)
p) -(¾x+2y)-(-½x-y-2)
r) (-⅗ab+2,6a)-(-0,6ab+2 i ⅗a)
s) 1-[-4x+(3+5x)]
t) -2,4x-[-(x+1)+(1,4x-1)]
u) [5ab-(4a+3b)]-[-6a-(4b-5ab)]
w)-⅔ x + (-⅗y-⅚x)
x) ⅘x+[-(⅕x-1)-y-(0,4y-x)]
y) [0,8a-(-1,2a+0,4b)]-(2a-0,3b)+0,1b
z) -[-2a-(⅝a+0,4)]-[2½a+(⅛a-1,6)]

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-02-01T16:17:36+01:00
A) 3x+(2x+3y+1)=3x+2x+3y+1=5x+3y+1
b) -4y+(-y+3)=-4y-y+3=-5y+3
c) 5a+(5-4a)=5a+5-4a=a+5
d) 2x-3+(x+4)=2x-3+x+4=3x+1
e) x-6y+(-3x+7y)= x-6y-3x+7y=-2x+y
f) 2x-(3a-2)=2x-3a+2
g)a-(-2a+1)=a+2a-1=3a-1
h) 2y+6-(3y+5)=2y+6-3y-5=-y+1
i) (3-2x)-(2x-3)=3-2x-2x+3=6-4x
j) (x+2y-3)-(2x-3y+1)=x+2y-3-2x+3y-1=-x+5y-4
k) -(2x-3y+4z)-(5x-6y+7z)=-2x+3y-4z-5x+6y-7z=-7x+9y-11z
l) (2x-1)+(3x-2)-(4x-6)=2x-1+3x-2-4x+6=x+3
ł) (-y+4)-(2y-1)+(3y+3)=-y+4-2y+1+3y-3=2
m) (x-5)-(2x-1)-(-x+4)=x-5-2x+1+x-4=-8
n) (x-4y+1)-(x+3y-4)+(3x-y+5)=x-4y+1-x-3y+4+3x-y+5=3x-8y+10
o) (8x-y)-(3x+y)-(-5x-2y)=8x-y-3x-y+5x+2y=10x
p) -(¾x+2y)-(-½x-y-2)=-¾x-2y+½x+y+2=-½x-y+2
r) (-⅗ab+2,6a)-(-0,6ab+2 i ⅗a)=-⅗ab+2,6a+0,6ab-2⅗a=0
s) 1-[-4x+(3+5x)]=1-(-4x+3+5x)=1+4x-3-5x=-2-x
t) -2,4x-[-(x+1)+(1,4x-1)]=-2,4x-(-x-1+1,4x-1) = -2,4x+x+1-1,4x+1=-2,8x+2
u) [5ab-(4a+3b)]-[-6a-(4b-5ab)]=(5ab-4a-3b)-(-6a-4b+5ab)= 5ab-4a-3b+6a+4b-5ab=2a+b
w)-⅔ x + (-⅗y-⅚x)=-⅔ x -⅗y-⅚x=-4/6x -3/5y -5/6x= -1i3/6x -3/5y = -1,5x-0,6y
x) ⅘x+[-(⅕x-1)-y-(0,4y-x)]=⅘x+(-⅕x+1-y-0,4y+x)= ⅘x-⅕x+1-y-0,4y+x=1i3/5x+1-1,4y
y) [0,8a-(-1,2a+0,4b)]-(2a-0,3b)+0,1b= 0,8a+1,2a-0,4b-2a+0,3b+0,1b=0
z) -[-2a-(⅝a+0,4)]-[2½a+(⅛a-1,6)]= -(-2a-⅝a-0,4)-(2½a+⅛a-1,6)= 2a+⅝a+0,4-2½a-⅛a+1,6= 2a + 5/8a +0,4 -2i4/8a -1/8a +1,6 = 2-2/8a=2-1/4a

to było długie mam nadzieje że dodasz jako najlepsze. pozdro